Accuracy of intraocular lens power calculation for cataract surgery after deep anterior lamellar keratoplasty. (6th December 2021) - Pellegrini, Marco; Furiosi, Luca; Salgari, Niccolò; D'Angelo, Sergio; Zauli, Giorgio; Yu, Angeli Christy; Busin, Massimo
Abstract: Background: The purpose of this study was to assess the accuracy of intraocular lens power (IOL) formulas for cataract surgery after deep anterior lamellar keratoplasty (DALK). Methods: This retrospective study included eyes which had previously undergone DALK and underwent standard phacoemulsification with monofocal IOL implantation between January 2012 and January 2021 at Ospedali Privati Forlì "Villa Igea" (Forlì, Italy). The predicted spherical equivalent (SE) was calculated using the Barrett Universal II, Emmetropia Verifying Optical (EVO), Haigis, Hoffer Q, Hoffer QST, Holladay 1, Holladay II, Kane and SRK/T formulas. Prediction error (PE) was calculated as the actual postoperative SE refraction minus the SE predicted refraction. Results: Eighty‐two eyes of 82 patients were included. The mean PE was negative using all formulas. Friedman test revealed a statistically significant difference of the median absolute PE (MedAE) among the different IOL formulas ( P  = 0.005). On the basis of the MedAE, the formulas were ranked as follows: SRK/T (0.805 D), Kane (0.810 D), EVO (0.845 D), Hoffer QST (0.847 D), Barrett (0.895 D), Holladay 1 (0.915 D), Haigis (1.010 D) and Hoffer Q (1.070 D) formulas. Conclusions: All formulas had a tendency towards a myopic refractive shift in post‐DALK eyes. Although the SRK/T, Kane, EVO and Hoffer QST formulas were more accurate, predictability of refractive outcomes was lower than in virgin eyes.